Tetragonal to triclinic structural transition in the prototypical CeScSi induced by a two-step magnetic ordering: a temperature-dependent neutron diffraction study of CeScSi, CeScGe and LaScSi. (24th November 2016) - Ritter, C; Provino, A; Manfrinetti, P; Pathak, A K
Abstract: An investigation on the ground state magnetism of CeScSi, CeScGe (tetragonal CeScSi-type, tI 12, space group I 4/ mmm ) by temperature-dependent powder neutron diffraction has been carried out, as debated and controversial data regarding the low temperature magnetic behaviours of these two compounds were reported. Our studies reveal that, while cooling, long-range magnetic ordering in CeScSi and CeScGe takes place by a two-step process. A first transition leads to a magnetic structure with the Ce moments aligned ferromagnetically onto two neighbouring tetragonal basal a-b planes of the CeScSi-type structure; the double layers are then antiferromagnetically coupled to each other along the c -axis. The transition temperature associated with the first ordering is T N ~ 26 K and T N ~ 48 K for the silicide and the germanide, respectively. Here the spin directions are rigorously confined to the basal plane, with values of the Ce magnetic moments of μ Ce   =  0.8–1.0 μ B . A second magnetic transition, which takes place at slightly lower temperatures, results in a canting of the ordered magnetic moments out of the basal plane which is accompanied by an increase of the magnetic moment value of Ce to μ Ce   =  1.4–1.5 μ B . Interestingly, the second magnetic transition leads to a structural distortion in both compounds from the higher-symmetry tetragonal space group I 4/ mmm to the lower-symmetry and triclinic I –1 (non-standard triclinic). Magnetic symmetry analysis shows that the canted structure would not be allowed in the I 4/ mmm space group; this result further confirms the structural transition. The transition temperatures T S from I 4/ mmm to I –1 are about 22 K in CeScSi and 36 K in CeScGe, i.e. well below the temperature of the first onset of antiferromagnetic order observed in this work (or below the ordering temperature, previously reported as either T C or T N ). This result, along with the synchronism of the magnetic and structural transitions, suggests a magnetostructural origin of this structural distortion. We have also carried out powder neutron diffraction for LaScSi as a non-magnetically-ordering reference compound and compared the results with those of CeScSi and CeScGe compounds.